Konflik Pekerjaan-Keluarga dan Gangguan Mental Emosional pada Perawat Perempuan di Rumah Sakit Rujukan Nasional di Jakarta - Dewi Yunia Fitriani; Dewi Sumaryani Soemarko; Indra Hardjono; Astrid Sulistomo; Aria Kekalih (Majalah Kedokteran Indonesia, 2020)
Introduction: Emotional mental disorder (EMD) is a state of psychological distress that, if not handled properly, can lead to severe mental disorders. One potential psychosocial hazard that is thought to be related to mental health disorders is work-family conflict (WFC). The issue of family-work balance has become an important issue among Indonesian female workers, especially with the rapidly growing female worker society and the strong family culture. This study aimed to identify the association between work-family conflict and emotional mental disorder in female nurses. Methods: This cross-sectional study included 264 female nurses who work at national referral general hospital in Jakarta. Their emotional mental disorder was measured using Self-Reported Questionnaire 20 (SRQ-20) and the work-family conflict was measured using the Work-Family Conflict Scale (WCFS). Results: The prevalence of emotional mental disorder in female nurses was 23.5%. The most dominant factor associated with emotional mental disorder is work-family conflict (OR 2,40, CI 95% 1,32-4,35, p=0,004). Conclusion: There is a significant association between work-family conflicts and emotional mental disorders in female nurses in Indonesia. Nurses with work-family conflicts are more likely to have emotional mental disorders. Regular mental health checks and counseling should be performed along with periodic health checks.